2011
DOI: 10.1088/0031-9155/56/3/018
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of small electron fields collimated by the integrated photon MLC

Abstract: In this study, a Monte Carlo (MC)-based beam model for an ELEKTA linear accelerator was established. The beam model is based on the EGSnrc Monte Carlo code, whereby electron beams with nominal energies of 10, 12 and 15 MeV were considered. For collimation of the electron beam, only the integrated photon multi-leaf-collimators (MLCs) were used. No additional secondary or tertiary add-ons like applicators, cutouts or dedicated electron MLCs were included. The source parameters of the initial electron beam were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…These parameters are iteratively adjusted to achieve an agreement with measurement data. 20,29,32,33 It should be noted that inaccuracies in modeling the source distribution and the geometry, position, and material composition of Linac components, especially of the in-field treatment head components such as the ionization chamber and scattering foil can affect the final dose distribution. 34 While direct measurement of electron beam T VI.…”
Section: A Vendor Parameter Tuningmentioning
confidence: 99%
“…These parameters are iteratively adjusted to achieve an agreement with measurement data. 20,29,32,33 It should be noted that inaccuracies in modeling the source distribution and the geometry, position, and material composition of Linac components, especially of the in-field treatment head components such as the ionization chamber and scattering foil can affect the final dose distribution. 34 While direct measurement of electron beam T VI.…”
Section: A Vendor Parameter Tuningmentioning
confidence: 99%
“…Various groups [1][2][3][4][5] have reported on the feasibility of using the photon MLC as a possible collimation device, while others [6][7][8][9][10][11][12] have manufactured add-on electron MLCs that are positioned closer to the patient in an effort to minimize the penumbra width due to air scatter. It was reported that acceptable penumbra can be obtained with photon MLCs by using SSDs in the 70 cm range.…”
Section: Introductionmentioning
confidence: 99%
“…Various groups have been investigating an efficient and clinically practical means to deliver MERT. Previous research on the electron MLC (eMLC) for MERT delivery is documented in representative literatures by Ma et al, (2) Gauer et al, (10) Hogstrom et al, (11) Al-Yahya et al, (12) Vatanen et al, (13) and Eldib et al, (14) while efforts on using photon MLC (pMLC) to deliver MERT were also made by many investigators including du Plessis et al, (15) Klein et al, (16) Jin et al, (17) Karlsson et al, (18) and Mihaljevic et al (19) Recently, Connell et al (20) published a study on the use of scattering foil free beams for modulated electron radiotherapy, an experimental feasibility study on the use of scattering foil free beams for modulated electron radiotherapy, exploring the potential benefit of removing the scattering foil from the beam line due to the significant reduction of the bremsstrahlung tail dose.…”
Section: Introductionmentioning
confidence: 99%